Changes in Fatty Acids Profile, Health Indices, and Physical Characteristics of Organic Eggs from Laying Hens at the Beginning of the First and Second Laying Cycles - Zita, Lukáš; Okrouhlá, Monika; Krunt, Ondřej; Kraus, Adam; Stádník, Luděk; Čítek, Jaroslav; Stupka, Roman (Animals, 2022)
The present study compared the fatty acid profile and some physical parameters of eggs from hens reared according to the organic system at the beginning of the first and second laying cycle. A total of 1080 eggs were analysed at the beginning of the first (from the 28th to 30th week of age) and the second (from the 78th to 80th week of age) laying cycle. It was found that the hen ages influenced the egg weight, egg surface area, yolk proportion, and eggshell colour. Albumen and eggshell proportion, albumen, yolk index, Haugh unit score, and eggshell strength were lower in eggs from older hens compared with those produced from younger layers. Monounsaturated fatty acids were found in higher amounts than saturated fatty acids and polyunsaturated fatty acids in egg yolks of eggs from layers only at the beginning of the second laying cycle. The PUFAn-6/n-3 ratio, saturation, atherogenic, and thrombogenic indices were significantly lower in the egg yolks from older hens compared to younger layers. These findings (regarding the eggs from the older ones) prove that it is practical to utilize them in the organic farming system during a period of two years.
Keywords: thrombogenic; fatty acid; age; atherogenic; organic; laying hens